2015
DOI: 10.1021/jacs.5b06815
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity with Topological Surface State in SrxBi2Se3

Abstract: By intercalation of alkaline earth metal Sr in Bi2Se3, superconductivity with large shielding volume fraction (∼91.5% at 0.5 K) has been achieved in Sr0.065Bi2Se3. Analysis of the Shubnikov-de Hass oscillations confirms the half-shift expected from a Dirac spectrum, giving transport evidence of the existence of surface states. Importantly, SrxBi2Se3 superconductor is stable under air, making SrxBi2Se3 an ideal material base for investigating topological superconductivity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

29
298
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(330 citation statements)
references
References 28 publications
29
298
2
1
Order By: Relevance
“…However, whether or not the Cu x Bi 2 Se 3 is a topological superconductor is still controversial. Recently, we found that an alternative compound, Sr x Bi 2 Se 3 , exhibits superconductivity with high superconducting volume fraction [21]. The following investigations have revealed that the atomic position of Sr in Sr x Bi 2 Se 3 is completely different from that of Cu in Cu x Bi 2 Se 3 .…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…However, whether or not the Cu x Bi 2 Se 3 is a topological superconductor is still controversial. Recently, we found that an alternative compound, Sr x Bi 2 Se 3 , exhibits superconductivity with high superconducting volume fraction [21]. The following investigations have revealed that the atomic position of Sr in Sr x Bi 2 Se 3 is completely different from that of Cu in Cu x Bi 2 Se 3 .…”
mentioning
confidence: 92%
“…That is, the copper atoms are intercalated in the weakly van der Waals bonded Se-Se layers, while most of the intercalated strontium atoms are located in the Se-Bi-Se-Bi-Se quintuple layer [22]. Furthermore, the Sr x Bi 2 Se 3 compounds exhibit well-separated topological surface state from the bulk bands [21][22][23][24]. These facts suggest that the Sr x Bi 2 Se 3 compound exhibits interesting physical phenomena and could serve as an important material base for the investigation of topological superconducting-related properties.…”
mentioning
confidence: 99%
“…For clean and perfect surface, the SABSs should be detectable. Recently, the possible existence of surface states in superconducting Sr x Bi 2 Se 3 is inferred from the Shubnikov-de Hass oscillation measurement [30]. In combination with the results of the present work, it is therefore highly desirable to reexamine the existence of the SABSs in Cu x Bi 2 Se 3 as a crucial test for the relevancy of the proposed SC pairing [11,22,31].…”
Section: Introductionmentioning
confidence: 67%
“…To date, possible topological superconductivity has been suggested in Cu-or Sr-intercalated Bi 2 Se 3 [19][20][21][22][23][24][25], In-doped SnTe [26], highly-pressured Bi 2 Te 3 and Sb 2 Te 3 [27,28], point-contact induced pressure in Cd 3 As 2 [29], and hybrid superconductor-semiconductor or -topological insulator heterostructures [30][31][32]. However, Pd-Bi family [33][34][35] of superconductors are particularly interesting because both Bi and Pd atoms intrinsically maintain strong spin-orbit coupling (SOC).…”
Section: Introductionmentioning
confidence: 99%